2003
DOI: 10.2134/jeq2003.2272
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Release of Cesium‐137 by Five Plant Species as Influenced by Soil Amendments in Field Experiments

Abstract: Phytoextraction field experiments were conducted on soil contaminated with 0.39 to 8.7 Bq/g of 137Cs to determine the capacity of five plant species to accumulate 137Cs and the effects of three soil treatments on uptake. The plants tested were redroot pigweed (Amaranthus retroflexus L. var. aureus); a mixture of redroot pigweed and spreading pigweed (A. graecizans L.); purple amaranth (A. cruteus L.) x Powell's amaranth (A. powellii S. Watson), referred to here as the amaranth hybrid; Indian mustard [Brassica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 20 publications
3
11
0
2
Order By: Relevance
“…This new technology employs the use of higher plants capable of accumulating high levels of contamination in shoots. Following harvesting the shoot biomass can be disposed of a final repository after volume reduction (ashing) (Fuhramnn et al, 2004). The present investigation demonstrates that sunflower can tolerate uranium to a certain level and hence can be used to filter contaminated runoff and in hazardous radioactive waste sites.…”
Section: Discussionmentioning
confidence: 74%
“…This new technology employs the use of higher plants capable of accumulating high levels of contamination in shoots. Following harvesting the shoot biomass can be disposed of a final repository after volume reduction (ashing) (Fuhramnn et al, 2004). The present investigation demonstrates that sunflower can tolerate uranium to a certain level and hence can be used to filter contaminated runoff and in hazardous radioactive waste sites.…”
Section: Discussionmentioning
confidence: 74%
“…Substantial species variation in Cs accumulation from soils has been demonstrated, but no special hyperaccumulator type was identified [244]. Researchers compared a number of species relative uptake of Cs and found that red root pigweed (Amaranthus retroflexus L.) accumulated much higher shoot Cs levels than other studied species [245,246]. Redroot pigweed bioaccumulated Cs from soils into shoots, while most other species accumulated Cs in roots.…”
Section: Phytoextraction Of Other Soil Elementsmentioning
confidence: 99%
“…Such factors include soil type and properties (CEC, specific sorption properties, and the nature and amount of organic and mineral matter) (Manjaiah et al, 2003;Lembrechts, 1993;Monira et al, 2005), radionuclide interaction with the soil, level of potential sorptioncompetitive species in the soil solution, and type of crop. In addition to the radionuclide fraction available in the soil, the CEC of the soil, the solid-liquid distribution coefficient (K d ) and levels of competitive species (K + and NH 4 + ) for radiocesium can be used for prediction purposes (Absalom et al, 2001;Fuhrmann et al, 2003).…”
Section: Introductionmentioning
confidence: 99%